Where Are We Heading in Terms of Eco-Innovation? Recent Evidence from Slovakia - Daniela RYBÁROVÁ; Mária KMETY BARTEKOVÁ; Slavka ŠAGÁTOVÁ (Communications of International Proceedings, 2022)
The research goal of the study is to identify the development of the eco-innovation implementation and to evaluate the progress in the attitudes of Slovak entrepreneurs towards eco-innovations between 2011 and 2021. Our research paper builds on the results of the Flash Eurobarometer 315 survey (2011) and a similar survey only within the companies operating in the Slovak Republic in 2021 (after 10 years since from Flash Eurobarometer 315 survey. In our research, we have set five research questions linked to the attitudes to eco-innovation in the Slovak enterprises. Our sample consists of 300 enterprises in agriculture, forestry and fishing, manufacturing, water supply, sewerage, waste management and remediation activities, construction, and food and beverage service activities. The relevant sample size should be 306 for a population of 244,000 (Z-score 1.96) at a confidence level of 95% (industry standard) and a margin of error of 5.6%. In 2011, new or a significantly improved eco-innovative production process or method (24.3%) and new or a significantly improved eco-innovative organizational innovation (22.6%) prevailed. According to the survey, in 2021 it showed a shift in direction to new or significantly improved eco-innovative product or service to the market (28.9%). The increase in the number of respondents who have introduced at least one variant of eco-innovation in the last 2 years from 41% to 43% is also positive.
Keywords: Barriers of Eco-innovations; Eco-innovation; Flash Eurobarometer 315; Slovakia; Sustainable production.